2012
DOI: 10.1158/1055-9965.epi-12-0426
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fertility Drugs and Risk of Ovarian Cancer: Results from a U.S.-Based Case–Control Study

Abstract: Background Previous studies examining associations between use of fertility drugs and ovarian cancer risk have provided conflicting results. We used data from a large case-control study to determine whether fertility drug use significantly impacts ovarian cancer risk when taking into account parity, gravidity, and cause of infertility. Methods Data from the Hormones and Ovarian Cancer Prediction (HOPE) study were used (902 cases, 1802 controls). Medical and reproductive histories were collected via in-person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 61 publications
2
35
0
1
Order By: Relevance
“…This resulted in the elimination of the following numbers of cases: breast (3 cases within 1 year, 31 within 2 years), endometrial (0,0), ovarian (0,3), in situ cervix (3, 17), invasive cervix (2, 5). These eliminations did not substantially change the interpretation of risks associated with different fertility treatments.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in the elimination of the following numbers of cases: breast (3 cases within 1 year, 31 within 2 years), endometrial (0,0), ovarian (0,3), in situ cervix (3, 17), invasive cervix (2, 5). These eliminations did not substantially change the interpretation of risks associated with different fertility treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the latest National Immunization Survey data in McLaughlin et al, 2007;Antoniou et al, 2009;Moorman et al, 2009;Jordan et al, 2010;Titus-Ernstoff et al, 2010;PermuthWey et al, 2011;Tsilidis et al, 2011;Jordan et al, 2012;Kurta et al, 2012;Le et al, 2012;Pieta et al, 2012;Weiderpass et al, 2012;Wilailak et al, 2012;Su et al, 2013). Some studies indicate that breastfeeding lowers risk of developing ovarian cancer (Risch et al, 1983;CSHS, 1987;Harlow et al, 1988;Gwinn et al, 1990;Whittemore et al, 1992;Siskind et al, 1997;Salazar-Martinez et al, 1999;Greggi et al, 2000;Modugno et al, 2001;Tung et al, 2003;Mills et al, 2004;Rossing et al, 2004;Huusom et al, 2006;McLaughlin et al, 2007;Moorman et al, 2009;Jordan et al, 2010;Titus-Ernstoff et al, 2010;Permuth-Wey et al, 2011;Jordan et al, 2012;Kurta et al, 2012;Pieta et al, 2012;Wilailak et al, 2012;Su et al, 2013), while many other studies observed no associations between breastfeeding and ovarian cancer risk (Mori et al, 1988;Booth et al, 1989;<...>…”
Section: Introductionmentioning
confidence: 99%
“…An increased risk of ovarian cancer with ovulation-inducing drug use was suggested in two early studies (2, 3), whereas recent cohort studies among infertile women suggest no association (410). Concerns, however, persist given reports of increased risk among certain subgroups of women, namely increased risk among women who remain nulligravid despite ovulation-inducing drug use (2, 1113), increased risk with extended follow-up (12), and increased risk of borderline ovarian tumors (3, 9, 14, 15). The inconsistent results may be due to methodological limitations of the studies.…”
mentioning
confidence: 99%